Analysis of Elements that Form Employee Job Satisfaction at CV. Ibnu Aqil Mandiri: - Atika Aini Nasution; Aan Nurhadi (ProBisnis : Jurnal Manajemen, 2023)
From the initial research that researchers did, the phenomenon within the company was related to the employees' work awareness for the organization, where it was an obligation that needed to be further developed. For that reason the clarity of goals and policies applied by the organization is a very important factor and needs to be implemented properly and correctly so that employee job satisfaction with the organization can grow. Of course employee job satisfaction can grow along with the creation of a conducive organizational climate. The warmth of the work relationship at the workplace, the organization's attention to the facilities and infrastructure that are increasingly adequate, the better employee rewards need to get the attention of superiors because these factors contribute positively to employee job satisfaction. The purpose of this research is to find out the elements that influence the formation of employee job satisfaction on the CV. Ibnu Aqil Mandiri. The number of samples in this study amounted to 10 people using saturated sample techniques. The analysis technique used is descriptive analysis method. The results showed that the most dominant factors affecting employee job satisfaction CV. Ibnu Aqil Mandiri is a desire for a decent life. This is based on the desire to get compensation in the form of basic salary, incentives in the form of additional bonuses outside of basic salary, benefits such as THR, leave due to illness, leave because of the interests of holding a marriage, pregnancy and so forth. Likewise with career development, job allowances, family allowances that play a role as a driver of his desire to work harder and improve his abilities.